Transnational corporations and climate change: towards a global governance framework - Banerjee, Bobby (Henry Stewart Talks, 2011)
Global corporate citizenship, Corporate responses to climate change, The politics of climate change, Climate change or climate justice?, Carbon as a commodity, Why political economy?, The political economy of climate change, Trade related intellectual property rights, Inclusions and exclusions, Global governance of the political economy, Democratic governance of the political economy, From responsibility to accountability, Global governance, Questions